IMPACT OF CENTRAL BANK OF NIGERIA-EFINA FINANCIAL INCLUSION PROGRAMME ON THE WELLBEING OF WOMEN BENEFICIARIES IN SOUTHWESTERN NIGERIA - Olalekan Olalekan; Oluwaseun Matina; James; Sunday Augustine (Bajang Institute, 2023)
The study ascertained the impact of impact of central bank of Nigeria-EFInA financial inclusion programme on the wellbeing of women beneficiaries in Southwestern Nigeria. Specifically, we evaluated the socio-economic characteristics of women beneficiaries, the constraint associated with respondents in accessing different actors in the financial inclusion program and the impact of the CBN-EFInA Financial Inclusion Program on the respondents’ well-being. A descriptive survey design was used to achieve our objectives. Two hundred and forty (240) questionnaires were distributed to respondents, out of which two hundred (200) were fully completed and used for the analysis. From our findings, majority of the respondents were in their active age, and were involved in trading as a business venture. The respondents were low income earners, there were more respondents at the bottom of pyramids. Most of the respondents could afford to open a bank account and also had access to seamless savings in their bank accounts. The study concluded that the CBN EFInA Financial inclusion program had positive impacts on the respondents’ well-being. It was recommended that women should be encouraged to open accounts with financial institutions, also there should be presence of banks in the unbanked areas so as to increase women’ financial inclusion